Drug resistance mechanisms and novel drug targets for tuberculosis therapy. (20th January 2017) - Islam, Md Mahmudul; Hameed, H.M. Adnan; Mugweru, Julius; Chhotaray, Chiranjibi; Wang, Changwei; Tan, Yaoju; Liu, Jianxiong; Li, Xinjie; Tan, Shouyong; Ojima, Iwao; Yew, Wing Wai; Nuermberger, Eric; et al.
Abstract: Drug- resistant tuberculosis (TB) poses a significant challenge to the successful treatment and control of TB worldwide. Resistance to anti- TB drugs has existed since the beginning of the chemotherapy era. New insights into the resistant mechanisms of anti- TB drugs have been provided. Better understanding of drug resistance mechanisms helps in the development of new tools for the rapid diagnosis of drug- resistant TB. There is also a pressing need in the development of new drugs with novel targets to improve the current treatment of TB and to prevent the emergence of drug resistance in Mycobacterium tuberculosis . This review summarizes the anti- TB drug resistance mechanisms, furnishes some possible novel drug targets in the development of new agents for TB therapy and discusses the usefulness using known targets to develop new anti- TB drugs. Whole genome sequencing is currently an advanced technology to uncover drug resistance mechanisms in M. tuberculosis . However, further research is required to unravel the significance of some newly discovered gene mutations in their contribution to drug resistance.